Guía práctica para la correcta manipulación de productos farmacéuticos según normas GDP (2022)
International trade enables than all the countries around the world can supply their needs thanks to the exchange of goods, historically the exchange and commerce has been a fundamental part of the society growth and progress. Each country has an advantage compared with other countries, it depends on their geographic location and resources. For example, those countries who has not a direct connection to the sea can stock up of fishes and seafood thanks to the international trade